The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12282-011-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

The roles of TGF-β signaling in carcinogenesis and breast cancer metastasis

Abstract: Transforming growth factor-β (TGF-β) ligand is a multifunctional growth factor that regulates various cell behavior, such as cell proliferation, differentiation, migration, and apoptosis. Because TGF-β is a potent growth inhibitor, abnormalities in TGF-β signaling result in carcinogenesis. In addition to tumor suppressor function, TGF-β acts as an oncogenic factor. In particular, TGF-β signaling plays an important role during metastasis of breast cancer. Recently, epithelial-mesenchymal transition (EMT) has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
126
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 59 publications
3
126
0
Order By: Relevance
“…The TGF-β growth factor cytokine family is composed of a large number of secreted polypeptides that activate cellular responses involved in development, homeostasis and the immune system (92). In addition, TGF-β1 signalling has been widely reported to have a dual role in the progression of cancer.…”
Section: Transforming Growth Factor-beta 1 (Tgf-β1) Signalling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The TGF-β growth factor cytokine family is composed of a large number of secreted polypeptides that activate cellular responses involved in development, homeostasis and the immune system (92). In addition, TGF-β1 signalling has been widely reported to have a dual role in the progression of cancer.…”
Section: Transforming Growth Factor-beta 1 (Tgf-β1) Signalling Pathwaymentioning
confidence: 99%
“…In addition, TGF-β1 signalling has been widely reported to have a dual role in the progression of cancer. While it acts as a tumour suppressor and inhibits cell proliferation during the early stages of carcinogenesis, it promotes migration and metastasis in the late stages of the disease (92). Similar to TBX3, TGF-β1 signalling is critical for the development of the mammary glands but also contributes to breast cancer progression through the inhibition of cell proliferation and promotion of migration (93).…”
Section: Transforming Growth Factor-beta 1 (Tgf-β1) Signalling Pathwaymentioning
confidence: 99%
“…In the advanced stage of carcinogenesis, TGF-acts as an oncogenic factor and induces invasion-associated epithelial-mesenchymal transition. TGF-is thought to enhance tumor growth and invasion through regulation of immune functions and angiogenesis, as well as the production of stromal components [42]. TGF-is secreted as a latent complex containing one of the LTBPs.…”
Section: Latent Transforming Growth Factor β Binding Proteinsmentioning
confidence: 99%
“…While TGFβ1 inhibits cell growth at an early stage of carcinogenesis, it supports metastasis formation in late‐stage cancer (Imamura et al ., 2012). We have previously shown that TGFβ signaling and TGFβ receptor type‐2 (TGFBR2) seem to have a tumor promoting role in human estrogen receptor (ER)‐negative breast cancer (Keklikoglou et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%